Exploring the Feelings of International Students: When We Learn Virtually during the COVID-19 Pandemic - Puspitasari, Dewi; Rahayu, Wiwien Widyawati; Rohmatunnazilah; Suwarno (Journal of International Students, 2020)
This narrative study aims to explore the feelings of two Indonesian students studying in Saudi Arabia and the Netherlands in relation to their learning experience during the COVID-19 pandemic. Data were garnered from semi-structured interviews and were analyzed with Martin and White’s language appraisal (2005) theory as well as Bourdieu’s cultural capital and Giddens’ structuration theories. Findings showed that the participants experienced dissatisfaction and insecurity during the learning process. However, they demonstrated adaptability and coping strategies manifested through making peace with themselves.